Analyzing the Equilibrium State of Government Budget Function: Reviewing the Data of Egypt - Eltahir, Yassin; Badr, Abdallah; M. Alobaid, Hussain.; Yousif Mousa, Elsiddig; Omer Osman, Hussien (AFEBI Economic and Finance Review, 2024)
The study aims to analyze the budget surplus function using differential equations to evaluate equilibrium values, sensitivity, and stability. To achieve this objective, the study employed various variables representing fiscal and monetary policy tools, as well as mixed policy instruments. Time series data were collected for two distinct periods: the first spanning from 2004 to 2011, and the second covering 2012 to 2021.The results indicate that equilibrium values increased for all variables in the second period compared to the first, with the exception of the exchange rate. Most variables became more influential on the budget surplus in the second period, except for the exchange rate and investment. The stability analysis revealed that the budget surplus function was unstable in both periods, with a slight preference for the first period based on the indicators observed. The study concludes that fiscal policy tools had a relatively stronger impact compared to monetary policy tools in addressing the Egyptian budget surplus during the period from 2004 to 2021.